Thermoplastic Elastomer Foams Based on Recycled Rubber. Issue 5 (September 2014) - Mahallati, Paridokht; Rodrigue, Denis
In this work, different concentrations (0, 35, 50 and 65%wt.) of recycled rubber (ethylene-propylene diene, EPDM) were blended with virgin polypropylene (PP) to produce thermoplastic elastomer resins via twin-screw extrusion. Then, the samples were pelletized and foamed by injection molding using a chemical blowing agent (azodicarbonamide, ADC). In particular, the molding process was optimized to determine the effect of processing parameters like blowing agent content, mold temperature, and injection conditions (pressure, velocity, etc.). From the samples obtained, a complete morphological (skin thickness, cell size and cell density) and mechanical characterization was performed including density and hardness. The results obtained showed that it is more difficult to produce a good foam structure with increasing recycled rubber content.